Perbandingan Ketentuan Perlindungan Hukum Upah Minimum Negara Mesir Dengan Indonesia Prespektif Keadilan Jhon Rawls - Jaedin Jaedin; Tri Budiyono; Jumiarti Jumiarti (Universitas Wahid Hasyim Semarang, 2020)
Abstract Legal protection for minimum wages provides certainty for a living wage. Minimum wage policy with the aim of achieving balance and fairness for workers and employers. However, the minimum payment must not be used after demonstrations every year to raise the minimum wage, as well as the minimum payment policy for each different district and city, causing turmoil in each region. So, with the decentralization policy of minimum wages in Indonesia, there are still many pros and cons, while in Egypt, the centralized model policy only sets minimum wages, national level, closer to welfare, John Rawls, in relation to distributive equality.